Сертификация по стандарту PCI DSS - Галата, Д.П.; Корниенко, Б.Я.; Галата, Л.П. (Моделювання та інформаційні технології, 2010)
The PCI DSS is a multifaceted security standard that includes requirements for
security management, policies, procedures, network architecture, software design and
other critical protective measures. This comprehensive standard is intended to help
organizations proactively protect customer account data. Compliance to PCI DSS
standards is truly a mandatory rule for business merchants who opt to accept payments
through the use of plastic cards such debit and credit cards.